Treatment of Malignant Peritoneal Mesothelioma - Levý, Miroslav; Boublíková, Ludmila; Büchler, Tomáš; Šimša, Jaromír (Klinicka onkologie, 2019)
Malignant mesothelioma is a highly malignant disease that most often occurs in the pleura of the thoracic cavity, followed by the peritoneum, pericardium, or tinea vaginalis testis. Malignant peritoneal mesothelioma (MPM) accounts for 10-15% of all mesotheliomas. The most significant risk factor for MPM is exposure to asbestos. There is no specific symptomatology, and imaging (computed tomography) and histopathology are crucial for diagnosis. There are no generally accepted guidelines for radical treatment of MPM. Previously, the prognosis of MPM patients was poor, with survival of up to 1 year. However, median survival of patients who are suitable candidates for radical therapy is currently 3-5 years. A combination of cytoreductive surgery (CRS) and hyperthermic perioperative chemotherapy (HIPEC) is recommended in selected patients, while chemotherapy alone has insufficient efficacy. Systemic chemotherapy remains the only treatment option for patients who are unsuitable for CRS and HIPEC. In selected patients scheduled for or currently undergoing CRS and HIPEC, surgery may be performed in combination with systemic chemotherapy in the neoadjuvant or adjuvant setting; however, the benefit is unclear. There are no recommendations for follow-up of MPM patients after radical surgery. Existing guidelines for the pleural form (e.g., those issued by the European Society for Medical Oncology) do not specify the frequency or method of investigation. In the absence of specific serum markers, only CA 125 and mesothelin are generally available. Imaging methods include ultrasonography, computed tomography, and magnetic resonance imaging.
Keywords: intraperitoneal chemotherapy; mesothelioma; Mesothelioma; Combined Modality Therapy; indukovaná hypertermie; Humans; mezoteliom; lidé; Hyperthermia, Induced; Peritoneal Neoplasms; peritoneální nádory; cytoreductive surgery; kombinovaná terapie; cytoredukční chirurgie; Cytoreduction Surgical Procedures